DARI BAITUL HIKMAH KE PERPUSTAKAAN MODERN: EVOLUSI DAN PERAN PERPUSTAKAAN DALAM DINAMIKA PERADABAN ISLAM - Jamila; Andi Abdul Hamzah; Darussalam Syamsuddin (JIMR : Journal Of International Multidisciplinary Research, 2026)
This study aims to understand the evolution and role of libraries in the dynamics of Islamic civilization from the Baitul Hikamah (House of Wisdom) to the modern library. The method used is a qualitative study with a historical-descriptive approach through literature analysis. The results reveal that in classical times, such as the Bayt al-Hikamah, it functioned as an intellectual center focused on knowledge production, although access was still limited to elite circles. In the modern era, libraries have undergone major changes through the digitization of collections and services, as well as the adoption of the concept of social inclusion that has made libraries more open and user-oriented. Thus, the development of libraries in Islamic civilization shows a continuous shift from exclusive to inclusive institutions, from physical to digital collections, and from centers of knowledge production to centers of community empowerment.